College choice factors and individual characteristics of Senior High School students and their implications for institutional policy and decision-making - JUAREZ, LAURICE FAYE (Archīum Ateneo, 2018)
Students college choice is a complex process which involves several stages and multiple factors, and hold implications for institutional policy makers. This study described the individual characteristics of 138 senior high school students of a private school in Bataan province and identified the important college choice factors to them. It further examined whether there were significant relationships between the respondents individual student characteristics and the college choice factors. Computing for the Chi-square test of independence revealed that there were generally no significant relationship between the individual student characteristics and the college choice factors save for (1) aptitude and Advice of Significant Persons and (2)aspiration and Institutional Characteristics. The findings indicate that the respondents aptitude is related to how they ascribed importance to theAdvice of Significant Persons, and that their level of educational aspiration isrelated to their assessment of Institutional Characteristics. The findings are generally not supported by the literature. Further studies on college choice inthe Philippine context is suggested which could hopefully lead to local modelof college choice.